Emergence, Evolution and Economics of Coronaviruses - Sidhant Jain; Meenakshi Rana; Pooja Jain (European Journal of Biology)
Viruses are the most abundant biological entities on our planet. On the basis of parameters like capsid structure, morphology, genetic material, etc., they are classified into different families. The Coronaviridae family of viruses includes a diverse group of positive strand RNA viruses and a subset of these viruses infects humans. Though some of these human-infecting coronaviruses cause minor respiratory ailments in healthy adults but three of them are responsible for major pandemics of the 21st century. These pandemics claimed thousands to several hundred thousands of human lives and have plunged the regional economies and even the global economy into an abyss. This work highlights the current research on human coronaviruses involving their diversity, evolution, clinical, and zoonotic attributes. An economic impact analysis of major coronaviruses is also presented to point out how these pathogens have claimed billions of dollars.